Entre notícias e formulários policiais: uma análise da construção midiática de jovens vítimas de crimes violentos nos periódicos Correio da Paraíba e Jornal da Paraíba - Aguiar, Tássio José Ponce de Leon (2015)
This research analyzed how newspapers Correio da Paraíba and Jornal da Paraíba reported news about young adults who were victims of violent crimes, in Cidades and Últimas sections, throughout a sample of 2014. The objective was to identify the meaning behind the choices made by both media, verifying aspects as the importance given to this kind of article, the published content’s diversity, the sources heard by the reporters, the news character, as well as the perceptions regarding youth, criminality and the individuals judged as deviants. The Content Analysis was the method chosen because it can identify the news tendencies, turning the raw data (like texts and images) into clear and justified statistics. The quantitative aspect also makes it possible to have a qualitative analytical approach, evaluating the details observed through the frequencies. In order to do it all, authors from communication, sociology, anthropology and Content Analysis were essential, such as Cremilda Medina, Mauro Wolf, Mar de Fontcuberta, Émile Durkheim, Howard Becker, Roberto DaMatta, Pierre Bourdieu, Mario Margulis, Marcelo Urresti, Michel Foucault, Laurence Bardin and Heloiza Herscovitz, debating themes as news values, crime, deviation, violence, youth and the methodological viability. Achieving the goals of this research, it was verified that, in general, both media reported news similarly: there is no consensual vision about what being young is like, nor any differential because of how young the victims are; both newspapers focus on answering the journalistic lead paragraph (who did what, when, where, how and why), only describing the occurrences by what they heard from official sources; there is no photographs attached, nor any highlights on the covers of the gazettes; mostly, there isn’t almost any purposed reflections concerning what those reported cases mean beyond what it is stated. Therefore, the media reports follow a standard, as if the journalist only answered to mandatory questions in a form. This is why the victims could be exchanged among the reports without any need to make changes on news’ structures. It’s clear though that both newspapers have potential to get over this kind of bureaucracy related to the way the reports are written and go much further on their narratives, as seen in other news about different subjects. However, it’s believed that this situation is due to the fact that both media don’t think the victimization of young adults is newsworthy enough, but keep posting about them in order to reinforce their panoptic social surveillance.